Палеоетноботанічні матеріали з НФ ІА НАН України зі слов’янських пам’яток - Горбаненко, С.А. (Археологія і давня історія України, 2014)
До наукового обігу введено нові дані з палеоетноботаніки з 8 слов’янських пам’яток І тис. н. е. Серед матеріалів поселення Сокільці виявлено обгорілі рештки зернівок культурних рослин, що виявилися «суржиком» пшениці карликової та жита. Проведено статистичний аналіз ПБС з 6 пам’яток другої половини І тис. н. е.: 2 празької культури, 4 райковецької культури. В научный оборот введены новые данные по палеоэтноботанике с 8 славянских памятников I тыс. н. э. (рис. 1). Часть материалов из-за незначитель- ного количества не представляет статистического интереса (табл.). На поселении Сокольцы обнаружена смесь зерновок пшеницы карликовой (Triticum compactum) и ржи (Secale cereale) (рис. 3): сурожь, характерная для посевов в средневековое время в Днестро-Прутском междуречье. Проведен статистический анализ ПБС 6 памятников второй половины I тыс. н. э.: 2 пражской культуры, 4 райковецкой культуры (рис. 4; 5). Основные выводы следующие. Носители пражской культуры выращивали несколько больше проса (Panicum miliaceum) и ячменя пленчатого (Hordeum vulgare), чем носители райковецкой культуры. Также замета определенная преемственность между ПБС памятников третьей и четвертой четвертей I тыс. н. э., находящимися невдалеке друг от друга (Рашков III — Рашков I; Лука-Каветчинская — Сокол). New palaeoethnobotanical materials from 8 Slavic sites of the I millennium BC are introduced to the scientific circulation. Some materials do not present statistical interest due to the small quantity. Found at settlement Sokoltsi is the mixture of seeds of specific wheat (Triticum compactum) and rye (Secale cereale): so called «surzhik» typical for sowing in the medieval period at the area between the Dnister and Prut Rivers. A statistical analysis of the palaeobotanic spectrum at 6 sites of the second half of the I millennium BC: 2 Prague culture and 4 Raykovetska culture sites. The main conclusions are as follows. The Prague culture population grew of millet (Panicum miliaceum) and barley (Hordeum vulgare) slightly more than Raykovetska culture bearers. Also noticed is a certain continuity between the palaeobotanic spectrum of sites dated by the third and fourth quarters of the I millennium BC and located not far from each other (Rashkiv III — Rashkiv I; Luka Kavetchinska — Sokol).